2009
DOI: 10.1002/asna.200911311
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale magnetic flux concentrations from turbulent stresses

Abstract: In this study we provide the first numerical demonstration of the effects of turbulence on the mean Lorentz force and the resulting formation of large-scale magnetic structures. Using three-dimensional direct numerical simulations (DNS) of forced turbulence we show that an imposed mean magnetic field leads to a decrease of the turbulent hydromagnetic pressure and tension. This phenomenon is quantified by determining the relevant functions that relate the sum of the turbulent Reynolds and Maxwell stresses with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 40 publications
4
67
0
Order By: Relevance
“…Recently, direct numerical simulations (DNS) of both unstratified and stratified forced turbulence (Brandenburg et al 2010; hereafter referred to as BKR and BKKR, respectively) have substantiated this idea and have demonstrated that the effective magnetic pressure can indeed change sign. Similar results have now also been obtained for turbulent convection (Käpylä et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, direct numerical simulations (DNS) of both unstratified and stratified forced turbulence (Brandenburg et al 2010; hereafter referred to as BKR and BKKR, respectively) have substantiated this idea and have demonstrated that the effective magnetic pressure can indeed change sign. Similar results have now also been obtained for turbulent convection (Käpylä et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…A positive value of q s (but with large error bars) was originally reported for unstratified turbulence (Brandenburg et al 2010). Later, stratified simulations with isothermal stable stratification ) and convectively unstable stratification (Käpylä et al 2012) showed that it is small and negative.…”
Section: Active Regions and Their Inclination Anglementioning
confidence: 67%
“…The fact that this phenomenon can lead to an instability in a stratified layer was first found in mean-field models (Brandenburg et al 2010Käpylä et al 2012), and more recently in DNS . However, NEMPI has not yet been able to explain flux concentration in the direction along the mean magnetic field, i.e., the largescale structures remain essentially axisymmetric.…”
Section: Active Regions and Their Inclination Anglementioning
confidence: 83%
“…We therefore adopted a simple α quenching prescription to arrange the field strength to be in the desired range. Furthermore, unlike much of the earlier work on NEMPI, we used an adiabatic stratification here instead of an isothermal one; see Brandenburg et al (2010) and Käpylä et al (2012) for earlier examples with adiabatic stratification in Cartesian geometry. An adiabatic stratification implies that the pressure scale height is no longer constant and now much shorter in the upper layers than in the bulk of the domain.…”
Section: Discussionmentioning
confidence: 99%
“…Direct numerical simulations (DNS; see Brandenburg et al 2011;Kemel et al 2012a), mean-field simulations (MFS; see Brandenburg et al 2010Brandenburg et al , 2012Kemel et al 2012b;Käpylä et al 2012), and earlier analytic studies (Kleeorin et al 1989(Kleeorin et al , 1990(Kleeorin et al , 1996Kleeorin & Rogachevskii 1994;Rogachevskii & Kleeorin 2007) now provide conclusive evidence for the physical reality of NEMPI. However, open questions still need to be answered before it can be applied to detailed models of active regions and sunspot formation.…”
Section: Introductionmentioning
confidence: 93%